A Curriculum for Achieving Universal Health Care: A Case Study of Ateneo de Zamboanga University School of Medicine - Guignona, Monserrat; Halili, Servando; Cristobal, Fortunato; Woolley, Torres; Reeve, Carole; Ross, Simone Jacquelyn; Neusy, André-Jacques (Frontiers in Public Health, 2021)
Introduction: Universal Health Care requires equal distribution of a health workforce equipped with competencies appropriate for local population needs. While health inequities persist in the Philippines, the Ateneo de Zamboanga University School of Medicine (ADZU-SOM) in Zamboanga Peninsula – an impoverished and underserved region – has demonstrated significant success retaining graduates and improving local health statistics. This study describes the qualitative evidence of ADZU-SOM students and graduates having positive impacts on local health services and communities, and the contextual factors associated with the school's socially-accountable mission and curriculum that contribute to these impacts. Methods: This qualitative study involved 41 one-on-one or group interviews conducted across seven participant groups (faculty, graduates, final-year students, health professionals, health workers, community members, community leaders). Gale et al's method for analyzing qualitative data in multi-disciplinary health research, WHO's “6 Building Blocks for quality health systems” framework and THEnet's social-accountability framework were used to organize and interpret data. Results: Local community members, community leaders, and health staff consistently reported examples of ADZU-SOM students and graduate doctors developing health infrastructure and providing health education, health promotion, and disease prevention activities accessible to all population groups. Students and graduates suggested these impacts were due to a number of factors, including how ADZU-SOM's sandwich model of longitudinal community-engagement culminating in 10-months continuous community placement in the final year helped them develop a strong motivation for community service, the teachings and curriculum activities that focused on public health and the social determinants of health, and faculty's commitment and ability to operationalize ADZU-SOM's mission and values. Staff also reported impacts were driven by integration of regional and national health priorities as core curriculum, and involving local stakeholders in curriculum development. Conclusions: This study provides qualitative evidence that ADZU-SOM's curriculum content and immersive community placements are training a medical workforce that is strengthening local health systems and health infrastructure across all 6 WHO “Building Blocks for quality health systems.” These findings suggest ADZU-SOM has managed to evolve a consciousness toward community service among final year students and graduates, adding evidence to the assertion it is a fully socially-accountable health professions institution.